Effectiveness of interactive dashboards as audit and feedback tools in primary care: A systematic review - Florence L. Meier; Levy Jäger; Oliver Senn; Stefan Markun; Jakob M. Burgstaller (PLoS ONE, 2025)
Interactive audit and feedback dashboards, which summarize performance using quality indicators, are increasingly used to enhance care processes and outcomes, but their effectiveness in primary care remains underexplored. This systematic review aimed to evaluate the impact of these dashboards in primary care settings by analyzing studies that compared their use to usual care or similar interventions without dashboards. A comprehensive search across MEDLINE (via Ovid), Embase, Cochrane Library, Scopus, and Web of Science through November 2024 was conducted. Risk of bias was assessed using Cochrane tools, and evidence quality was evaluated with GRADE. Relevant data, including features of the interactive dashboards, were extracted, and findings were synthesized narratively and visualized with forest plots. Six studies met the inclusion criteria, comprising five randomized controlled trials and one non-randomized trial, all with low or moderate risk of bias. Four studies incorporating dashboards into multifaceted interventions showed improvements in at least one primary outcome, while two studies using standalone dashboards reported mixed results. Significant heterogeneity in dashboard design, study settings, targeted health conditions, and quality indicators limits the generalizability of these findings. Nonetheless, the results highlight the potential of interactive dashboards to improve quality indicators performance in primary care, particularly as part of broader intervention strategies. Standardized evaluation frameworks and rigorous, consistent reporting are needed in future research to better isolate the effects of interactive dashboards and enhance the robustness and applicability of the evidence in varied primary care contexts. Registration Prospero (CRD42024506727).